Komunikasi Lisan Dengan Tatap Muka Dalam Era Teknologi Komunikasi Organisasi Di Perpustakaan IAIN Pontianak - Fahrizandi Fahrizandi; Tiara Al Dhera (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Despite the rapid development of the quantity of devices and the quality of multifunctional communication media technology, it is not yet strong enough to completely replace the advantages possessed by face-to-face oral communication. This article aims to describe face-to-face oral communication in the era of organizational communication technology at the IAIN Pontianak Library. This study uses a descriptive qualitative approach, technical data collection using interviews, observation, and documentation. The results of the research findings are first, face-to-face oral communication applied at the IAIN Pontianak Library aims to convey information, regulations, and stimuli for work that takes place every day according to the situation in the library environment with formal and non-formal communication between the head of the library, coordinator and library staff. Second, the supporting factors for face-to-face oral communication are close space, feel more comfortable, have a sense of kinship, and establish friendship. Third, the inhibiting factors of face-to-face oral communication include being out of place, difficulty managing time, and language difficulties when communicating orally.